Hierarchical dynamic control for robust attitude tracking. Issue 2 (2020) - Invernizzi, Davide; Lovera, Marco; Zaccarian, Luca
Abstract: In this paper robust attitude tracking for fully actuated rigid bodies is addressed. By exploiting the cascade structure of the underlying mathematical model, a hierarchical framework including a large number of dynamic feedback controllers is proposed. The closed loop results in error dynamics comprising an inner loop associated with the angular velocity error, and an outer loop associated with the attitude error. We then establish sufficient conditions for solving the attitude tracking problem from an (almost) global perspective by leveraging recent results on stabilization of nonlinear cascades and invariance principles for differential inclusions. The modular nature of the proposed approach allows one to conclude stronger stability properties than those available for existing dynamic control laws, such as PID loops, often employed in applications.